Effects of Rice Bran Extract on Browning and Polyphenol Oxidase Activity in Vegetable and Fruit - Chockchai Theerakulkait; Kunnikar Boonsiripiphat (Agriculture and Natural Resources, 2007)
The effects of rice bran extract (RBE) on browning in potato, banana and apple slices compared with distilled water (DW) were investigated by measuring the changes of color values. Potato slice treated with RBE had lower browning value than that treated with DW during storage 9 to 12 hrs (p≤0.05). The browning values of potato treated with RBE and DW stored for 12 hrs were 4.72 and 7.64, respectively. Banana slice treated with RBE had lower browning value than that treated with DW during storage 2 to 12 hrs (p≤0.05). The browning values of banana treated with RBE and DW stored for 12 hrs were 19.76 and 27.17, respectively. Whereas, apple slice treated with RBE was slightly different from that treated with DW during storage 0 to 9 hrs. The browning values of apple treated with RBE and DW stored for 9 hrs were 5.21 and 7.84, respectively. Potato, banana and apple slices treated with RBE had higher L* value but lower a* value than that treated with DW. Regarding to the effect of RBE on polyphenol oxidase (PPO) activity. It was found that RBE had more inhibitory effect on PPO activity of potato than that of banana and apple with the %PPO inhibition of 96.11, 51.43 and 12.3, respectively. In conclusion, RBE could reduce browning and inhibit PPO activity in potato more than that of banana and apple.